The effects of land use and soil management on the physical properties of an Oxisol in Southeast Brazil - Seben Junior, Getulio de Freitas; Corá, José Eduardo [UNESP]; Lal, Rattan (Soc Brasileira De Ciencia Do Solo, 2014)
Soils of the tropics are prone to a decrease in quality after conversion from native forest (FO) to a conventional tillage system (CT). However, the adoption of no-tillage (NT) and complex crop rotations may improve soil structural quality. Thus, the aim of this study was to evaluate the physical properties of an Oxisol under FO, CT, and three summer crop sequences in NT: continuous corn (NTcc), continuous soybean (NTcs), and a soybean/corn rotation (NTscr). Both NT and CT decreased soil organic carbon (SOC) content, SOC stock, water stable aggregates (WSA), geometric mean diameter (GMD), soil total porosity (TP), macroporosity (MA), and the least limiting water range (LLWR). However they increased soil bulk density (BD) and tensile strength (TS) of the aggregates when compared to soil under FO. Soil under NT had higher WSA, GMD, BD, TS and microporosty, but lower TP and MA than soil under CT. Soil under FO did not attain critical values for the LLWR, but the lower limit of the LLWR in soils under CT and NT was resistance to penetration (RP) for all values of BD, while the upper limit of field capacity was air-filled porosity for BD values greater than 1.46 (CT), 1.40 (NTscr), 1.42 (NTcc), and 1.41 (NTcs) kg dm(-3). Soil under NTcc and NTcs decreased RP even with the increase in BD because of the formation of biopores. Furthermore, higher critical BD was verified under NTcc (1.62 kg dm(-3)) and NTcs (1.57 kg dm(-3)) compared to NTscr and CT (1.53 kg dm(-3)).

A qualidade física dos solos sob clima tropical está sujeita à degradação, após a conversão de mata nativa em sistema de cultivo convencional (SCC). Entretanto, a adoção do sistema de semeadura direta (SSD) com a rotação de culturas proporciona melhorias à qualidade do solo. Assim, o objetivo deste estudo foi avaliar os atributos físicos de um Latossolo Vermelho sob mata nativa, SCC e SSD, envolvendo sequências de culturas de verão: Milho em Monocultura (SSD-MM), Soja em Monocultura (SSD-SM) e rotação soja/milho (SSD-RSM). As sequências de culturas sob SSD e SCC proporcionaram reduções no teor de carbono orgânico, no estoque de carbono, no índice de estabilidade de agregados (IEA), no diâmetro médio ponderado (DMP), na porosidade total (PT), na macroporosidade (MP) e no intervalo hídrico ótimo (IHO); no entanto, aumentaram a densidade do solo (DS) e a resistência tênsil dos agregados (RT), em comparação à mata nativa. O SSD proporcionou ao solo maiores valores de IEA, DMP, DS, RT e microporosidade e menores valores de PT e MP, em comparação ao SCC. O limite inferior do IHO no solo sob SSD e SCC foi a resistência à penetração para todos os valores de DS, enquanto o limite superior foi a porosidade de aeração para valores de DS acima de 1,46; 1,40; 1,42; e 1,41 kg dm-3 no solo sob SCC, SSD-RSM, SSD-MM e SSD-SM, respectivamente. No solo sob SSD-MM e SSD-SM, a redução da resistência à penetração com o aumento da DS pode ser atribuída à formação de bioporos. Além disso, a maior densidade crítica foi verificada sob SSD-MM (1,62 kg dm-3) e SSD-SM (1.57 kg dm-3) quando comparada ao SSD-RSM e SCC (1.53 kg dm-3).
Sistemas de uso e manejo do solo sobre os atributos físicos de um Latossolo no sudeste do Brasil
Keywords: No-tillage; Soil organic carbon; Soil aggregate; Bulk density; Tropical soil; Cerrado; Plantio direto; Carbono orgânico do solo; Agregado do solo; Densidade do solo; Solo tropical; Cerrado